Biopsychosocial Determinants of Long-term Contraceptive Use in Women of Reproductive Age in Surakarta, Central Java - Ratna Arifiana; Uki Retno Budihastuti; Isna Qadrijati (Journal of Health Promotion and Behavior, 2018)
Background: Family planning allows people to attain their desired number of children and determine the spacing of pregnancy. Long-term contraceptive methods are more effective, safe, with fewer contraindications than others contraceptive method. This study aimed to investigate the biopsychosocial determinants of long-term contraceptive use in women of reproductive age in Surakarta, Central Java, using a theory of planned behavior.Subjects and Method: This was an analytic observational study with a case-control design. The study was conducted in Surakarta, from January to February 2018. A sample of 210 women of reproductive age was selected for this study by fixed disease sampling. The dependent variable was long-term contraceptive use. The independent variables were age, parity, education, employment status, knowledge, attitude, subjective norm, perceived behavior control, husband support, family income, and health counseling. The data was collected by questionnaire and analyzed by path analysis.Results: Long-term contraceptive use increased with positive attitude (b=3.49; 95% CI= 1.88 to 5.11; p<0.001), supportive subjective norm (b= 2.91; 95% CI= 1.10 to 4.73; p=0.002), strong perceived behavior control (b=3.09; 95% CI= 1.29 to 4.88; p=0.001), and strong husband support (b=2.68; 95% CI= 1.04 to 4.33; p=0.001). Long-term contraceptive use was indirectly affected by knowledge, health conselling, and education level.Conclusion: Long-term contraceptive use increases with a positive attitude, supportive subjective norm, strong perceived behavior control, and strong husband support.Keywords: long-term contraceptive, the theory of planned behavior, path analysisCorrespondence: Ratna Arifiana, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: arifianaratna1301@gmail.com.Journal of Health Promotion and Behavior (2018), 3(1): 37-47https://doi.org/10.26911/thejhpb.2018.03.01.03